Sistem Pendukung Keputusan Metode ANP Dalam Menentukan Stasiun Televisi Terbaik - Destari, Ratih Adinda; Azhar, Asbon Hendra (LPPM STIKOM Tunas Bangsa, 2024)
Television media is an information technology that displays images and sound, where television is a communication medium that provides various updated information and disseminates it to the public. At this time there are so many television stations that there is increasingly competition among television stations to provide interesting programs, these television stations are competing in terms of providing innovation and information and there are those who compete only to attract the public's attention so that the television station's programs get attention. high rating to seek its own profit. To overcome the above problems, a decision support system is needed where the method uses the Analytical Network Process (ANP) method, which this method is used because it can provide the best decision based on the highest value to the lowest value and will provide recommendations to the public which television stations can be recommended as worthy. watched by the public according to the needs of the community. From the calculation results, it was found that RCTI had a value of 0.3775, SCTV had a value of 0.1954, Indosiar had a value of 0.1770, TV One had a value of 0.1363 and Kompas TV had a value 0,0325